Effects of Shape, Roughness and Gloss on the Perceived Reflectance of Colored Surfaces - Honson, Vanessa; Huynh-Thu, Quan; Arnison, Matthew; Monaghan, David; Isherwood, Zoey J.; Kim, Juno (Frontiers in Psychology, 2020)
This study examined perceptual differentiation of specular from diffuse shading for the recovery of surface colour and gloss. In Experiment 1, we parametrically varied the mesoscale relief height of globally planar surfaces, specular sharpness and the orientation of the surface relative to the light source. We obtained psychophysical matches for perceived colour saturation and value (HSV), but also considered whether the main effects could be influenced by colour space used when transforming data to perceptually-uniform CIE LCH space. Results revealed strong interactions between perceived colour attributes and the lighting conditions, the structure of specular reflections, and surface relief. Declines in saturation were observed with increasing specular roughness (using an HSV colour representation), but no similar decline was observed in chroma (using a CIE LCH colour representation). Experiment 2 found strong negative correlations between perceived gloss and specular roughness. Perceived gloss also depended on mesoscopic relief height and orientation of the surface relative to the light source. Declines in perceived gloss moderately accounted for the variability in colour saturation and value matches obtained in Experiment 1. We found information about perceived specular coverage could further improve the model’s accountability of perceived colour saturation and lightness (Experiment 3). These findings together suggest that perceived colour saturation and colour value depends on the visual system’s ability to distinguish the underlying diffuse shading from specular highlights in images.